2003
DOI: 10.1139/s03-001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of drinking water quality in ten small Quebec utilities

Abstract: A comparative study relating to distributed water quality was undertaken in 10 small municipal drinking water utilities in Quebec. All of these utilities apply direct chlorination to surface water or groundwater under the direct influence of surface water without any previous treatment. These utilities were divided into two groups: four utilities that had never or rarely served water violating the provincial drinking water microbiological standards (relating to fecal and (or) total coliform bacteria) and six u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…To consider such variations, DBP seasonal thresholds were modified specifically for this index application to take account of realistic seasonal objectives (Table 2). DBPs are also contaminants that have a particularly variable occurrence from location to location within the distribution system (Coulibaly and Rodriguez 2003;Summerhayes et al 2011;Uyak et al 2014). Moreover, this spatial variability can change seasonally.…”
Section: Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…To consider such variations, DBP seasonal thresholds were modified specifically for this index application to take account of realistic seasonal objectives (Table 2). DBPs are also contaminants that have a particularly variable occurrence from location to location within the distribution system (Coulibaly and Rodriguez 2003;Summerhayes et al 2011;Uyak et al 2014). Moreover, this spatial variability can change seasonally.…”
Section: Scenariomentioning
confidence: 99%
“…Understanding the simultaneous variability of different water quality parameters at different time scales (e.g., days, months, and seasons) could help small-system operators take better decisions to improve overall water quality. In fact, various studies have shown that spatio-temporal variations of drinking water can be significant (Coulibaly and Rodriguez 2003;Al Khatib 2005;Giannoulis et al 2004) and that said variations are based mainly on the variability of source water quality (Sharp et al 2006;Ouyang et al 2006;Wei et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics were considered according to a previous study bearing on the same 10 utilities (Coulibaly and Rodriguez, 2003b). The considered raw water quality variables were total organic carbon (TOC), turbidity, total coliform bacteria, heterotrophic plate count (HPC) bacteria and atypical bacteria.…”
Section: Raw Water Quality Variablesmentioning
confidence: 99%
“…Like raw water quality variables, these characteristics were taken from a previous study on the same 10 utilities (Coulibaly and Rodriguez, 2003b). Table 1 provides an overview of the spatial variation of water quality from the source (i.e.…”
Section: Distributed Water Quality Variablesmentioning
confidence: 99%
“…Some common water quality indicators used for water distribution are turbidity, residual disinfectant, pH, nitrates, phosphates, organic compounds, total/fecal coliforms, and heterotrophic bacteria (HPC) (Coulibaly and Rodriguez, 2003;Hunsinger and Zioglio, 2002;Clark, 1994).…”
Section: Introductionmentioning
confidence: 99%